Modular endoprosthetic implant for maximizing residual limb length: A case report. (February 2019) - El Beaino, Marc; Liu, Jiayong; Lin, Patrick P
Background: For transfemoral amputations, the residual femoral length is critically important to prosthetic function. The aim of this report is to describe a novel method of extending femoral length and to assess its stability over time. Case Description and Methods: A 57-year-old woman with recurrent parosteal osteosarcoma was treated with above-knee amputation. A portion of the distal femoral endoprosthesis, which included uncemented fixation with a Compress ® stem, was retained in an effort to extend the short femoral remnant and maximize stump length. Findings: At 3 years follow-up, the Compress stem remained well-fixed, and there was no soft tissue breakdown over the implant. The patient ambulated with a prosthetic limb and no external support. Outcomes and Conclusion: To the best of our knowledge, this is the first report of using the Compress device as a means to maintain stable fixation and extend residual femoral length following above-knee amputation. Clinical relevance: Extension of residual bone length in amputated limbs can help improve prosthetic fitting and function. The Compress device may be useful in this application as a means of secure fixation for a modular metallic prosthesis.